Salmonella Typhi Haplotype 58 biofilm formation and genetic variation in isolates from typhoid fever patients with gallstones in an endemic setting in Kenya - Muturi, Peter; Wachira, Peter; Wagacha, Maina; Mbae, Cecilia; Kavai, Susan M.; Mugo, Michael M.; Mohamed, Musa; González, Juan F.; Kariuki, Samuel; Gunn, John S. (Frontiers in Cellular and Infection Microbiology, 2024)
Although typhoid fever has largely been eliminated in high-income countries, it remains a major global public health concern especially among low- and middle-income countries. The causative agent, Salmonella enterica serovar Typhi (S. Typhi), is a human restricted pathogen with a limited capacity to replicate outside the human host. Human carriers, 90% of whom have gallstones in their gallbladder, continue to shed the pathogen for an ill-defined period of time after treatment. The genetic mechanisms involved in establishing the carrier state are poorly understood, but S. Typhi is thought to undergo specific genetic changes within the gallbladder as an adaptive mechanism. In the current study, we aimed to identify the genetic differences in longitudinal clinical S. Typhi isolates from asymptomatic carriers with gallstones in a typhoid endemic setting in Nairobi, Kenya. Whole-genome sequences were analyzed from 22 S. Typhi isolates, 20 from stool samples, and 2 from blood samples, all genotype 4.3.1 (H58). Out of this, 19 strains were from four patients also diagnosed with gallstones, of whom three had typhoid symptoms and continued to shed S. Typhi after treatment. All isolates had point mutations in the quinolone resistance-determining region (QRDR), and only sub-lineage 4.3.1.2.EA3 encoded multidrug resistance genes. There was no variation in antimicrobial resistance patterns among strains from the same patient/household. Non-multidrug resistant (MDR) isolates formed significantly stronger biofilms in vitro than the MDR isolates, p<0.001. A point mutation within the treB gene (treB A383T) was observed in strains isolated after clinical resolution from patients living in 75% of the households. For missense mutations in Vi capsular polysaccharide genes, tviE P263S was also observed in 18% of the isolates. This study provides insights into the role of typhoid carriage, biofilm formation, AMR genes, and genetic variations in S. Typhi during asymptomatic carriage.